PEMODELAN EKSPANSI STENT JANTUNG DENGAN BALON HYPER - ELASTIS - Donny Suryawan; Suyitno Suyitno (Teknoin, 2016)
Coronary artery disease (CAD) is a disease that most cause mortality in Indonesia. CAD is caused by cholesterol-containing deposit (plaque) that make the coronary artery become narrow and can cause a heart attack. Stent implantation is the most common treatment to opens or alleviates the narrowing coronary artery. A preliminary study has done to simulate the expansion of coronary stent with negligible balloon method. The negligible balloon is less accurate and far from realistic condition because it neglects the presence of the balloon. This study has proposed another method to simulate the stent expansion. Hyper-elastic balloon method is used to investigate the stress distribution, outer diameter change, and dogboning phenomena of the stent.